2021
DOI: 10.1111/anu.13371
|View full text |Cite
|
Sign up to set email alerts
|

Potassium diformate in the diet of sterlet sturgeon ( Acipenser ruthenus ): Zootechnical performance, humoral and skin mucosal immune responses, growth‐related gene expression and intestine morphology

Abstract: This study evaluated the dietary effect of potassium diformate (KDF) on growth performance, body composition, humoral and skin mucosal immune responses, growthrelevant gene expression and intestine histomorphology in sterlet sturgeon. Sterlet fingerlings (N = 270; 6.86 ± 0.14 g) were scattered randomly into 18 tanks (six experimental diets in triplicate groups) and fed with incremental levels of KDF including 0 (control), 3 (KDF 3 ), 6 (KDF 6 ), 9 (KDF 9 ), 12 (KDF 12 ) and 15 (KDF 15 ) g kg −1 for 70 days.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
2
1
Order By: Relevance
“…However, dietary supplementation of KDF at 12 and 15 g/kg did not improve growth performance in hybrid tilapia [39]. Kakavand et al [40] observed similar effects of improved KDF in the freshwater sturgeon, sterlet (Acipenser ruthenus), but the concentration used in their study was 9 g/kg feed, which is much higher than the concentration used in our study. Differences in nutrition and digestive system structure between A. ruthenus and H. huso may account for the observed difference in concentration.…”
Section: Discussioncontrasting
confidence: 62%
“…However, dietary supplementation of KDF at 12 and 15 g/kg did not improve growth performance in hybrid tilapia [39]. Kakavand et al [40] observed similar effects of improved KDF in the freshwater sturgeon, sterlet (Acipenser ruthenus), but the concentration used in their study was 9 g/kg feed, which is much higher than the concentration used in our study. Differences in nutrition and digestive system structure between A. ruthenus and H. huso may account for the observed difference in concentration.…”
Section: Discussioncontrasting
confidence: 62%
“…Sotoudeh et al (2020) reported that administration of diets supplemented with blends of organic acids (sodium propionate and sodium acetate) for eight weeks increased plasma lysozyme and ACH50 of yellowfin seabream (Acanthopagrus latus) juveniles. Total immunoglobulin and lysozyme activity increased in the serum and skin mucus of sterlet sturgeon (Acipenser ruthenus) with increasing the dietary levels of potassium diformate (KDF) (Kakavand et al, 2021). In another study, Safari et al (2017) showed up-regulation of immune-related genes expression with increasing lysozyme activity and Ig level in the skin mucus of common carp (C. carpio) fed SP-supplemented dies for eight weeks.…”
Section: Discussionmentioning
confidence: 97%
“…organic acids and their salts effectively enhance the growth, nutrient utilization, and health status of aquatic animals (Agouz et al, 2015;Safari et al, 2016;Chow et al, 2017). These improvements are attributed to a significant decrease in pH of the gut and upper intestinal tract (Baruah et al, 2005;Abu Elala and Ragaa, 2015), an increase in the digestive enzyme activities (Su et al, 2014;Castillo et al, 2014), stimulating the growth of intestinal epithelial cells (Topping and Clifton, 2001;Gao et al, 2011;Kakavand et al, 2021), improvement in the digestibility of major nutrients (Morken et al, 2011), and altering the gut microbial community (Silva et al 2016). Van der Wielen (2002) reported that butyrate is less ideal as a feed additive for animals because of its quick absorption in the upper digestive tract.…”
mentioning
confidence: 99%